2021
DOI: 10.1093/mnras/stab3276
|View full text |Cite
|
Sign up to set email alerts
|

A map of diffuse radio emission at 182 MHz to enhance epoch of reionization observations in the Southern hemisphere

Abstract: We present a broadband map of polarized diffuse emission at 167-198 MHz developed from data from the Murchison Widefield Array (MWA). The map is designed to improve visibility simulation and precision calibration for 21 cm Epoch of Reionization (EoR) experiments. It covers a large swath—11,000 sq. deg.—of the Southern Hemisphere sky in all four Stokes parameters and captures emission on angular scales of 1○ to 9○. The band-averaged diffuse structure is predominantly unpolarized but has significant linearly pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…Because our maps are confusion limited they would form one part of a complete foreground model for EoR sciences, but can be used as-is for single-antenna total power measurements. Byrne et al (2021) have shown that the angular scale at which power of diffuse emissions and point sources are equal is in the order of several degrees, therefore diffuse sky maps such as these will be required for complete calibration models in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Because our maps are confusion limited they would form one part of a complete foreground model for EoR sciences, but can be used as-is for single-antenna total power measurements. Byrne et al (2021) have shown that the angular scale at which power of diffuse emissions and point sources are equal is in the order of several degrees, therefore diffuse sky maps such as these will be required for complete calibration models in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, baselines observing the North‐East and East‐North polarizations of the sky show a potential transition between galactic domination to point source or noise domination around 100 meters. At frequencies near the middle of the HERA band this corresponds to 1.5°, which is roughly the scale at which point sources are commensurate with galactic emission (Byrne et al., 2021). Given the significant agreement between our measured and expected distributions of C ij , we are confident in our conclusion that the observed structure in Figure 4 is driven by sky features rather than instrumental systematics.…”
Section: Cross‐correlation Metricsmentioning
confidence: 96%
“…We clearly see the smooth distribution we would expect from sky features, with clearly distinguishable sub‐groups by flagging categorization. We would expect a power law slope for galactic emission with strong variation as a function of baseline azimuthal angle, while the point source component should be independent of baseline length or angle, and noise should be similar to point sources (Byrne et al., 2021). Notably, the nominally good antennas generally follow this pattern, with a strong increase toward shorter baselines.…”
Section: Cross‐correlation Metricsmentioning
confidence: 99%
“…The analysis framework for our experiment is an opensource, EoR-specific pipeline composed of (1) Fast Holographic Deconvolution 4 (FHD; Sullivan et al 2012;Barry et al 2019a) and (2) Error Propagated Power Spectra with Interleaved Observed Noise 5 (εppsilon; Barry et al 2019a), hereafter called FHD/εppsilon. FHD/εppsilon has been used to generate competitive EoR upper limits (Beardsley et al 2016;Barry et al 2019b;Li et al 2019), investigate calibration systematics (Barry et al 2016;Li et al 2018;Byrne et al 2019;Zhang et al 2020), and probe subtleties in foreground and radio frequency interference subtraction (Carroll et al 2016;Pober et al 2016;Kerrigan et al 2018;Wilensky et al 2019Wilensky et al , 2020Byrne et al 2022). This analysis pipeline has been proven to be able to quantitatively characterize instrumental effects and spectral precision requirements for EoR science.…”
Section: Analysis Pipeline Sourcementioning
confidence: 99%